THE ROLE OF DIGITAL PLATFORM QUALITY IN SHAPING DONOR SATISFACTION AND LOYALTY: A STUDY ON RUMAH ZAKAT ONLINE DONATION SERVICES - Rusmayadi, Syaira Raditya; Rosinawati, Dian; Cahyanti, Irni Sri; Novita, Dwi (Journal of Management and Islamic Finance, 2025)
Rumah Zakat as a national zakat institution has adopted online donation services to facilitate the process of collecting funds. However, there are still problems with online donations that occur at Rumah Zakat, namely: system errors, virtual accounts, and pending transactions that affect donor satisfaction and loyalty at Rumah Zakat. So, this study aimed to 1) determine the implementation of online donation service quality 2) to determine the measurement of donor satisfaction and loyalty 3) to test the effect of online donation service quality on donor satisfaction and loyalty. This study used a quantitative method with a descriptive approach. Data collection techniques were carried out through questionnaires involving 100 donor respondents. The data were analyzed using simple linear regression by SPSS software version 25. The results showed that the quality of online donation services had a significant positive effect on donor satisfaction. And the quality of online donation services had a significant positive effect on donor loyalty. These findings confirm that improving service quality, such as reliability, responsiveness, assurance, empathy, and the physical appearance of the digital platform, can create a positive donation experience, to increase satisfaction, and encourage long-term donor loyalty to Rumah Zakat.